Localized TWIST1 and TWIST2 basic domain substitutions cause four distinct human diseases that can be modeled in Caenorhabditis elegans. (27th March 2017) - Kim, Sharon; Twigg, Stephen R.F.; Scanlon, Victoria A.; Chandra, Aditi; Hansen, Tyler J.; Alsubait, Arwa; Fenwick, Aimee L.; McGowan, Simon J.; Lord, Helen; Lester, Tracy; Sweeney, Elizabeth; Weber, Astrid; et al.
Abstract: Twist transcription factors, members of the basic helix-loop-helix family, play crucial roles in mesoderm development in all animals. Humans have two paralogous genes, TWIST1 and TWIST2, and mutations in each gene have been identified in specific craniofacial disorders. Here, we describe a new clinical entity, Sweeney-Cox syndrome, associated with distinct de novo amino acid substitutions (p.Glu117Val and p.Glu117Gly) at a highly conserved glutamic acid residue located in the basic DNA binding domain of TWIST1, in two subjects with frontonasal dysplasia and additional malformations. Although about one hundred different TWIST1 mutations have been reported in patients with the dominant haploinsufficiency Saethre-Chotzen syndrome (typically associated with craniosynostosis), substitutions uniquely affecting the Glu117 codon were not observed previously. Recently, subjects with Barber-Say and Ablepharon-Macrostomia syndromes were found to harbor heterozygous missense substitutions in the paralogous glutamic acid residue in TWIST2 (p.Glu75Ala, p.Glu75Gln and p.Glu75Lys). To study systematically the effects of these substitutions in individual cells of the developing mesoderm, we engineered all five disease-associated alleles into the equivalent Glu29 residue encoded by hlh- 8, the single Twist homolog present in Caenorhabditis elegans . This allelic series revealed that different substitutions exhibit graded severity, in terms of both gene expression and cellular phenotype, which we incorporate into a model explaining the various human disease phenotypes. The genetic analysis favors a predominantly dominant-negative mechanism for the action of amino acid substitutions at this highly conserved glutamic acid residue and illustrates the value of systematic mutagenesis of C. elegans for focused investigation of human disease processes.